Modern Artistic Space: the Problem of Anthropological and Aesthetic Transformation - E. A. Kapichina (Дискурс)
Introduction. The problem of analyzing the contemporary artistic space has its own evolution, its genesis is reduced to understanding different kinds of transformations in relation to the traditional art as a form of creative perception of reality based on spiritual values. As a result of the evolution of the creative process, most of the contemporary art practices, especially conceptual ones, «expel» anthropological and aesthetic origins from art. To understand why do such processes occur in the field of low-aesthetic reality, the author analyzes the problem of anthropological and aesthetic transformation of modern art, the main trends and place of a person in the contemporary artistic process.Methodology and sources. The author uses, first, hermeneutic methodology of analysis of artistic texts and conceptual approaches of authors; secondly, a set of artistic-aesthetic and artistic-historical methods aimed at identifying and generalizing materials, Dedicated to specific works of art; and, thirdly, philosophical-anthropological methodical analysis of the postmodern cultural situation and place of a person.Results and discussion. As a result of the discussions it was revealed that the characteristics of the current elitist conceptual practices of the postmodern period are: pluralism and offbeat from any canons; frank citation and borrowing; conceptualization of any gestures of the artist; the multiplicity of interpretations; multi-level perception; rejection of imagery; experimenting with new forms; creating the illusion of a «game of reality»; irony, pastiche, black humor and shock value; and finally, the author’s death and the loss of one’s own «I».Conclusion. In modern culture conceptualism becomes an articularized form of expression of the artistic consciousness of postmodernism. As art moves beyond its boundaries, it completely transforms its ontological foundations, then its anthropological core disappears and the author’s «death» occurs. The products of conceptual creativity are some kind simulacrums of language, style or symbols, which simulate pre-existing human values. Such art neantisates person with traditional values, perverts the meaning of creativity itself, transforms the aesthetic and the anthropological attitudes of the creative process.